RANCANGAN FORMULIR UNTUK MEREKAM KEGIATAN DAN TRANSAKSI KEUANGAN GKPS HOSIANNA PEMATANGSIANTAR - Djuli Sjafei Purba (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2021)
This community service aims to create documents / forms that will be used to record various activities and financial transactions that occur in the Hosianna GKPS and are used as an accountability report to the Congregation at the end of the year. The service implementation method begins with studying the characteristics of the activities and cash flows that occur. Then a form is designed that can record various types of financial activities and transactions. From the study, twenty-four forms and one receipt were obtained. And it is hoped that the results of this dedication will enable allstakeholders to understand and use the form that has been designed and ensure the accuracy of financial information and data. To ensure the achievement of the objectives of this service, for 4 months assistance was provided in filling out the various forms.